2020
DOI: 10.1080/1331677x.2020.1782242
|View full text |Cite
|
Sign up to set email alerts
|

Competition, diversification and performance in dual banking: a panel VAR analysis

Abstract: This article investigates the dynamic relationship among competition, diversification and bank performance using data for 18 countries with a dual banking system over the period 2000 to 2016. Analyses using panel vector autoregression (P.V.A.R.) model, impulse response function (I.R.F.) and variance decomposition (V.D.C.) methods confirm that market power increases the profitability and the stability of banks the dual banking system while revenue diversification reduces them. Market power increases revenue div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Islamic banks should pay more attention to non-financing sources of income such as investments and other income that do not violate sharia rules (Le et al, 2022). Sahul Hamid and Ibrahim (2021) also find a significant impact of diversification on the performance of the dual banking system. Interestingly, diversification can damage the profitability of the dual banking system in developing countries but not emerging countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Islamic banks should pay more attention to non-financing sources of income such as investments and other income that do not violate sharia rules (Le et al, 2022). Sahul Hamid and Ibrahim (2021) also find a significant impact of diversification on the performance of the dual banking system. Interestingly, diversification can damage the profitability of the dual banking system in developing countries but not emerging countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the earlier studies, return on asset was considered essential for banks and other loanproviding institutions (Alzahrani & Alfares, 2021;Bhattarai, 2018;Edi & Wijaya, 2022;Pereira et al, 2022;Ramachann et al, 2022;Service, 2021;Wynn, 2021), because the survival of these institutions is directly dependent on return on asset. In this regard, the banks' management should ensure that the loans provided by the banks are appropriate as they can be returned safely to the owners (Hamid & Ibrahim, 2021;Partovi & Matousek, 2019;Petkovski et al, 2018; Pilinkienė et al, 2021;Qin et al, 2021;Ribaudo, 2020;Sell, 2020;Tetrevova et al, 2021). Indeed, in America and United Kingdom the banks are working with strict laws related to return on investment and if the people are not willing to pay the banks (Farooq et al, 2019;Sigurdsson et al, 2021;Wang et al, 2020), the administration takes strict actions against the defaulters.…”
Section: Return On Asset Return Of Equity Economic Sustainability Pol...mentioning
confidence: 99%
“…wrote that macro prudential policies came to the fore in countries implementing Islamic finance, especially after the 2008 crisis. Hamid & Ibrahim (2020) employing panel vector autoregression models on 18 countries between the period 2000 to 2016 documented that that market power increases stability and profitability in dual banking system. Maghyereh & Yamani (2022) reported that the covid-19 pandemic affected conventional and Islamic banks equally in terms of systematic risk.…”
Section: Literature Reviewmentioning
confidence: 99%